Applying the Intervention Model for Fostering Affective Involvement with Persons who Are Congenitally Deafblind: An Effect Study. (September 2014) - Martens, Marga A. W.; Janssen, Marleen J.; Ruijssenaars, Wied A. J. J. M.; Huisman, Mark; Riksen-Walraven, J. Marianne
Introduction: In this study, we applied the Intervention Model for Affective Involvement (IMAI) to four participants who are congenitally deafblind and their 16 communication partners in 3 different settings (school, a daytime activities center, and a group home). We examined whether the intervention increased affective involvement between the participants and their communication partners and whether it increased positive emotions and reduced negative emotions in the participants. Methods: We used video observations in a multiple-baseline design across subjects to assess the effects of the 20-week intervention on the communication partners' interactions with the participants. Results: After onset of the intervention, affective involvement increased for three participants, while all four participants showed an increase in positive emotions and a decrease in negative emotions. During follow-up, the positive effect on the participants' behaviors decreased in most cases, but remained visible as compared to the baseline level. Discussion: The findings demonstrate that the IMAI can be successfully applied to persons who are congenitally deafblind. Given the small number of participants, replication of the intervention is recommended. Implications for practitioners: Affective involvement can be increased by training, but it is difficult to maintain this effect over time. Coaching of communication partners on a more permanent basis is recommended to maintain the sharing of emotions between persons who are congenitally deafblind and their communication partners.